2017
DOI: 10.1186/s40413-017-0163-2
|View full text |Cite
|
Sign up to set email alerts
|

The grass pollen season 2015: a proof of concept multi-approach study in three different European cities

Abstract: BackgroundGrasses release the most widespread aeroallergens with considerable sensitization rates, while different species produce several pollen concentration peaks throughout the season. This study analyzed the prevalence of grass species in three different European city areas and compared the flowering period of these species with daily pollen concentrations and the symptom loads of grass pollen allergy sufferers.MethodsThe most prevalent grass species in Vienna (Austria), Berlin (Germany) and Turku (Finlan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 29 publications
(36 reference statements)
3
16
0
Order By: Relevance
“…However, we found that Phleum made up a very small proportion of metabarcoding reads ( Supplementary Figure 1), corresponding with the results of an earlier phenological study 9 .…”
supporting
confidence: 89%
See 1 more Smart Citation
“…However, we found that Phleum made up a very small proportion of metabarcoding reads ( Supplementary Figure 1), corresponding with the results of an earlier phenological study 9 .…”
supporting
confidence: 89%
“…However, despite the harmful impact of grass pollen on human health, especially as reported in developed nations, current studies and forecasts categorize grass pollen at the family level (Poaceae) 6,7 due to difficulties in differentiating species based on morphology 8 . Furthermore, while different species of temperate grass flower at different timepoints 9,10 , it is unknown if the disparate phenology of local grass taxa at ground level are useful for making predictions on the seasonal variation in airborne pollen. Airborne pollen is highly mobile 11,12 and pollen concentrations often do not directly correlate to local flowering times 11 .…”
mentioning
confidence: 99%
“…Species such as Phleum pratense have been identified to be a major source of allergenic pollen [5, 22]. However, we found that Phleum made up a very small proportion of metabarcoding reads (Fig 2), corresponding with the results of an earlier phenological study [23]. Most genera, such as Phleum, Anthoxanthum and Dactylis , show distinct and narrow temporal incidence (Fig 2), and could allow researchers to identify grass species associated with allergenic windows with greater accuracy.…”
Section: Resultssupporting
confidence: 85%
“…Data were selected and retrieved only for districts in Vienna (Austria) for the years 2013 until 2017 since user numbers are especially high from 2013 onwards. More than 50 entries per season allow a statistical analysis of a pollen season in terms of crowd-sourced symptom data [ 17 ]. This recommendation was far exceeded by daily mean entries of above 25 (see Area classification).…”
Section: Methodsmentioning
confidence: 99%
“…Pollen measurements are needed for the definition of a pollen season and for comparisons with the SLI (e.g. [ 15 , 17 ]). Thus, the SLI as a number on its own is independent of pollen data and calculated only on symptom data, but is in need for pollen data when a pollen season has to be defined as a prerequisite for a mean SLI in a certain period.…”
Section: Introductionmentioning
confidence: 99%